Effects of Multisport on the Development of Critical Thinking Abilities in Autism Patients (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Due to differences in neural processes, it can be hard for kids with autism to learn new thinking skills.  This different study looks at how well movement skill training works as a strategy to help kids with autism improve their cognitive skill development.  Our study, which focuses on Asian people, we hope will help make this problem clearer.  The first people to meet were parents of kids with autism spectrum disorder (ASD) to get more personal information about their kids.  Kids who have autism spectrum disorder (ASD) can keep track of their progress as they grow with the use of an evaluation instrument that measures their social and cognitive abilities Based on the results of this study.